Legendre Polynomials are Associated in the Schrodinger Polar Equation of Helium Ions - Bambang Supriadi; Eryna Dwicahyaning Krisnawanto; Ratih Wahyudianti; Mohammad Fathorrosi; Muhammad Najih Hamdi; Eka Citra Rahayu; Haniyah Alivia (Jurnal Penelitian Pendidikan IPA, 2024)
The helium ion is one of the ions classified as a hydrogenic atom because it has only one electron in its outer orbital so that the helium ion problem can be solved using the Schrodinger equation approach. The Schrodinger equation of the polar part of the helium ion can be solved by the associated legendary polynomial function, . The polar function expresses the angle formed by the vector of the electron's position relative to the z-axis of the helium ion's nuclear position. And it is produced that the polar function of the hydrogenic atom has the same polar function both in position space and in momentum space .